2015
DOI: 10.1098/rspb.2014.1857
|View full text |Cite
|
Sign up to set email alerts
|

Spatially heterogeneous impact of climate change on small mammals of montane California

Abstract: Resurveys of historical collecting localities have revealed range shifts, primarily leading edge expansions, which have been attributed to global warming. However, there have been few spatially replicated community-scale resurveys testing whether species' responses are spatially consistent. Here we repeated early twentieth century surveys of small mammals along elevational gradients in northern, central and southern regions of montane California. Of the 34 species we analysed, 25 shifted their ranges upslope o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 52 publications
4
133
0
2
Order By: Relevance
“…Several studies found that climate change caused heterogeneous shifts in the ranges of small mammals (Moritz et al 2008;Myers et al 2009;Rowe et al 2014). Similarly, our results also showed that changes in the eastern and western limits or the distribution center longitudes of several large mammal species could be attributed to climate change.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Several studies found that climate change caused heterogeneous shifts in the ranges of small mammals (Moritz et al 2008;Myers et al 2009;Rowe et al 2014). Similarly, our results also showed that changes in the eastern and western limits or the distribution center longitudes of several large mammal species could be attributed to climate change.…”
Section: Discussionsupporting
confidence: 82%
“…These characteristics may limit the variations in their ranges in response to climate change. Additionally, different mammal distributional changes may also be related to the spatially heterogeneous climate change in the QinghaiTibet plateau (Rowe et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our results seem to suggest that 1) mammalian elevation range shifts are not tightly coupled to climate or habitat, but of those that are 2) climate is the more important driver, albeit with a subsidiary role for habitat in shaping lower-edge range shifts. This suggests that different mechanisms that may underlie the Table 2 Observed elevational ranges of small mammals in the 1 Yosemite transect [5] compared with predictions from SDMs using climate, habitat, and climate + habitat predictors thresholded using the MSSS rule -no shift, C -contract, D -downward, U -upward, and NA -not applicable, i.e., when there was no convergence towards a model solution because the samples were all outside estimated range limits so no model was produced shifts in different parts of species' ranges [9,58]. However, our results may also implicate conflicting influences of climate and habitat on range shifts.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of natural history "big data" to explore organismal responses to environmental change has skyrocketed over the past decade (Rowe et al 2014;Rubidge et al 2011), the value of these resources to undergraduate education is just beginning to be realized . As the ease of accessing and analyzing the wealth of information in natural history collections continues to increase, the opportunities for creating significant and exciting learning experiences for students are growing.…”
Section: Big Data Big Opportunitiesmentioning
confidence: 99%
“…Because specimens and all associated data are both georeferenced and time-stamped, they provide critical resources for examination of changes in biodiversity over space and time (Johnson et al 2012;Lister 2011;Wandeler et al 2007). As a result, an increasing number of studies are using direct comparisons of historical and modern natural history specimens and associated information to document the impacts of climatic change (Moritz et al 2008;Rowe et al 2014;Tingley et al 2009). …”
Section: The Foundation: Climate Change Biodiversity and Natural Himentioning
confidence: 99%